Estimasi Pemberian Pinjaman Kredit Usaha Rakyat (KUR) di Bank BRI Unit Tangkerang Pekanbaru menggunakan Regresi Logistik - Safitri, Elfira; Hazirah, Azra; Rahmadeni, Rahmadeni (Zeta - Math Journal, 2024)
People’s Business Credit (KUR) is vulnerable to unwanted risks such as bad credit. The reduce bad credit, banks need to analyze whether customer debtors meet the requirements for credit. The aim of this research is to determine the logistic regression analysis model and determine the factors that influence the provision of People's Business Credit (KUR) at Bank BRI Unit Tangkerang Pekanbaru. The method used is the Logistic Regression method. Based on the research results, it was found that the factors that influence the provision of People's Business Credit (KUR) at Bank BRI Unit Tangkerang Pekanbaru are business turnover and business profit. So the logistic equation is obtained with the resulting logit function being g(x) = -11.587+0.501x_1+2.549x_2. The calcification value for granting People's Business Credit (KUR) using logistic regression is 93.84%.